Gender differences in the domains of job satisfaction: a questionnaire survey among doctors (Journal of Ideas in Health, 2020)
Background: The impact of gender differences in the labor market cannot be neglected when studying job satisfaction among doctors. This study aimed to assess the gender differences in a ten-items Warr–Cook–Wall (WCW) job satisfaction scale among Iraqi medical doctors. Methods: A cross-sectional study was conducted between January and June 2014 in Iraq. The multistage sampling technique was recruited to collect the data from 20 health institutions. A total of 576 doctors returned the self-administered questionnaire (response rate= 87.3%). Student t-test and the Pearson correlation tests were used to analyzing the data.Results:  Female doctors rated the overall job satisfaction index significantly higher than their peer male colleagues (P
Keywords: Gender Differences, Warr–Cook–Wall (WCW), Job Satisfaction, Doctors, Domains, Recognition, Iraq